Locomotor profile influences physiological and locomotor adaptations after 6 weeks of high-intensity or sprint interval training in male and female runners - Thron, M.; Sondermann, Y.; Ruf, L.; van Hooren, B.; Düking, P.; Wehdemeier, L.; Buday, L.; Woll, A.; Altmann, S. (International Journal of Sports Physiology and Performance, 2026)
Purpose: High-intensity interval training (HIIT) and sprint interval training (SIT) can improve physiological (eg, maximal oxygen uptake [VO2max]) and locomotor (eg, maximal aerobic speed, MAS; maximal sprinting speed, MSS) variables. However, the influence of an athlete`s locomotor profile on training adaptations to HIIT and SIT remains unclear. We aimed to (1) compare physiological and locomotor adaptations to HIIT and SIT and (2) assess how locomotor profiles affect these adaptations. Methods: Twenty-seven trained male and female runners (27.7 [7.5] y; n = 12 women) completed 6 weeks of HIIT (4-6 × 4 min @90%-95% MAS) or SIT (6-10 × 20-s all-out sprints), performed twice weekly. Pretest and posttests included 40-m sprinting (MSS) and incremental treadmill tests (VO2max, MAS, lactate thresholds [eg, v4mmo]). Anaerobic speed reserve was calculated as MSS minus MAS and speed reserve ratio as MSS divided by MAS. Linear mixed models and moderation analyses were performed. Results: Both HIIT and SIT significantly improved MAS (P <= .03). While only SIT enhanced MSS (interaction: P < .01), HIIT increased v4mmol (P < .01). In both groups, speed types (ie, higher speed reserve ratio and anaerobic speed reserve) showed greater MAS (P < .01) and v4mmol increases (P < .05) than endurance types (ie, lower speed reserve ratio and anaerobic speed reserve). Within the SIT group, endurance types improved MSS (P < .01) and VO2max more, while speed types increased VO2max more with HIIT (interaction: P <= .03). Conclusion: HIIT and SIT improve endurance outcomes in trained runners. Adaptations vary depending on locomotor profile, with speed types responding better to HIIT and endurance types benefiting more from SIT. Accordingly, individualizing training by locomotor profile may optimize outcomes.